Clinical Profile and Predictors of Mortality in Patients admitted with COVID-19 in a Tertiary Care Hospital - Shah, Syed Vaqar Ahmad; Ansari, Farmud; Sohrab, Sayed Sartaj; Alam, Kadir; Sarraf, Deependra Prasad (Nepal Medical College Journal, 2021)
Hospitalization and survival rate in patients with coronavirus disease 2019 (COVID-19) is affected by pre-existing chronic medical conditions and the disease severity. The objectives of the study were to describe the baseline clinical profile, co-morbidities, disease severity and to assess the predictors of mortality in hospitalized adult patients with COVID-19 in a tertiary care hospital in Nepal. A cross-sectional study was conducted for two months on 168 adult COVID-19 patients admitted to Nobel Medical College Teaching Hospital Biratnagar. Demographics, comorbidities, disease severity, oxygen requirement, and treatment outcomes were studied. The mean age of the patients was 57.1 years and 56.5% were male. Out of 168, 16.7% and 10.1% of the participants had currently or in the past used alcohol or tobacco products respectively. Hypertension (28.6%) and chronic lung disease (16.1%) were the most common co-morbidities. The overall case-fatality rate was 17.9%, with 32.1% and 56.3% in the severe and critical COVID-19 subgroup respectively. The mortality rate for patients without co-morbidities was 2.4% which increased to 63.6% for those with three or more co-morbidities. Age, disease severity, and the number of co-morbidities were found to be associated with increased mortality (P<0.05), whereas gender was not. The pre-existing chronic diseases and increased severity of the disease were associated with increased mortality in hospitalized COVID-19 adult patients.